THE ABILITY OF CRITICAL THINKING OF ELEMENTARY SCHOOL STUDENTS USING A GRAPHIC ORGANIZER INSTRUMENT - Otang Kurniaman; Eddy Noviana; Munjiatun Munjiatun (JMIE (Journal of Madrasah Ibtidaiyah Education), 2020)
Critical thinking is an emphasis on the 2013 curriculum, as an activity in learning that must be done by the teacher for that it needs analysis to describe student abilities. This research uses descriptive quantitative research method with a sample of 318 elementary school students who are in public schools in the Tampan District, Pekanbaru, Riau Province. The results of the study found that out of 18 schools with a sample of 318 students there were 9 schools that received the 'not good' category, 9 schools that received the 'not good' category. Viewed from the critical thinking indicator, it turns out that the student's ability score reaches 23 with the category of underperformance or very low under the standard of mastery learning. It can be concluded that the ability of students in critical thinking is still very low and needs government attention to improve teacher learning.